Some Smooth and Nonsmooth Traveling Wave Solutions for KP-MEW(2, 2) Equation - Liping He; Yuanhua Lin; Hongying Zhu (Journal of Mathematics)
In this paper, we consider the KP-MEW(2, 2) equation by the theory of bifurcations of planar dynamical systems when integral constant is considered. The periodic peakon solution and peakon and smooth periodic solutions are given.